BASLAWÍSH KLASS OQÍWSHÍLARÍNÍŃ KITAP PENEN ISLESIWINDE MUǴALLIM HÁM ATA-ANANÍŃ ǴAMQORLÍǴÍ - Abdijabbarova, J. (ILIM hám JÁMIYET, 2017)
The article deals with the mutual activity of teachers, parents and school children in the work with a book. The author of the article presents methods and gives recommendations how to develop the learner’s interest to readind books. The author also states about the importance of keeping the daily schedule.